Hydropower Production Benefits More From 1.5 °C than 2 °C Climate Scenario. Issue 5 (8th May 2020) - Meng, Ying; Liu, Junguo; Leduc, Sylvain; Mesfun, Sennai; Kraxner, Florian; Mao, Ganquan; Qi, Wei; Wang, Zifeng
Abstract: Hydropower plays an important role as renewable and clean energy in the world's overall energy supply. Electricity generation from hydropower represented approximately 16.6% of the world's total electricity and 70% of all renewable electricity in 2015. Determining the different effects of 1.5 and 2 °C of global warming has become a hot spot in water resources research. However, there are still few studies on the impacts of different global warming levels on gross hydropower potential. This study used a coupled hydrological and techno‐economic model framework to assess hydropower production under global warming levels of 1.5 and 2 °C, while also considering gross hydropower potential, power consumption, and economic factors. The results show that both global warming levels will have a positive impact on the hydropower production of a tropical island (Sumatra) relative to the historical period; however, the ratio of hydropower production versus power demand provided by 1.5 °C of global warming is 40% higher than that provided by 2 °C of global warming under RCP6.0. The power generation by hydropower plants shows incongruous changing trends with hydropower potential under the same global warming levels. This inconformity occurs because the optimal sites for hydropower plants were chosen by considering not only hydropower potential but also economic factors. In addition, the reduction in CO2 emissions under global warming of 1.5 °C (39.06 × 10 6  t) is greater than that under global warming of 2 °C (10.20 × 10 6  t), which reveals that global warming decreases the benefits necessary to relieve global warming levels. However, the hydropower generation and the reduction in CO2 emissions will be far less than the energy demand when protected areas are excluded as potential sites for hydropower plants, with a sharp decrease of 40–80%. Thus, government policy‐makers should consider the trade‐off between hydropower generation and forest coverage area in nationally determined contributions. Key Points: A coupled hydrological and techno‐economic model framework is used to assess hydropower production under global warming levels of 1.5 and 2 °C Production provided by 1.5 °C of global warming is greater than that provided by 2 °C of global warming under RCP6.0 Hydropower generation will be far less than the energy demand when protected areas are excluded as potential sites for hydropower plants